Expresión ¬((A∧B)∨(A∧C))
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(a∧b)∨(a∧c)=a∧(b∨c)¬((a∧b)∨(a∧c))=(¬b∧¬c)∨¬a
(¬b∧¬c)∨¬a
Tabla de verdad
+---+---+---+--------+
| a | b | c | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 1 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 0 |
+---+---+---+--------+
(¬a∨¬b)∧(¬a∨¬c)
Ya está reducido a FND
(¬b∧¬c)∨¬a
(¬a∨¬b)∧(¬a∨¬c)
(¬b∧¬c)∨¬a